Peran Etika Moral dan Akhlak dalam Kultur Makan: Studi Mini Riset pada Pengunjung Handayani Pujasera Kalimantan Kabupaten Jember - badriyah badriyah; Dewita Rahma Yuliana; Fahriza Salsabila Putri; Ivana Belda; Amelia Ayu Agustin; Fradila Cindi Riawan; Nafi' Ulya Nur; Agus Arifandi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Islam highly upholds ethical, moral and moral values in behavior. So the author wants to discuss the importance of ethics, morals, and morals in daily behavior. The awareness to behave well towards others is very important in today's life. Many young people today do not care about ethics, morals, and morals. This study aims to empirically prove the ethics, morals and morals of visitors to "Handayani Pujasera Kalimantan" when eating. We chose a research location in Handayani Pujasera Kalimantan where most of the visitors and buyers are students. This research uses qualitative methods. With collection techniques, namely interviews and observations. We interviewed several resource persons (students) who were in the food court to buy food. We interviewed about the urgency of ethics, morals and morals when eating. We also interviewed about the eating habits of visitors at the food court. And we ask about ethics, morals and good morals when eating. The results showed that the ethics, morals and morals of visitors to "Handayani Pujasera Kalimantan" when eating are good enough and knowledge of ethics, morals and morals when eating is very important to minimize irregular eating.